RETINOBLASTOMA IN AN OLDER CHILD: A CASE REPORT - Subedi, Kumudini; Dulal, Prachi; Parajuli, Srijana; Pradhan, Sangita (Journal of Chitwan Medical College, 2024)
Retinoblastoma is the most common intraocular malignancy of childhood. More than 90% of the patients are under 5-years old. It is uncommon in age above 5 years. In this study we report a case of retinoblastoma in a 9-year-old girl. She presented to our department with decreased vision in left eye noted for 6 days. Vision loss was non-progressive, associated with mild pain. Snellen’s acuity in the affected eye was light perception only. There were no signs of active inflammation in the anterior chamber. Anterior vitreous face demonstrated exuberant vitreous inflammation. A large, elevated, sessile lesion occupying the inferotemporal quadrant was seen just behind the lens with significant adjacent inflammation. Right eye examination was unremarkable. Ultrasound and Magnetic Resonance Imaging demonstrated retinoblastoma with no extra-ocular spread. Enucleation was done and biopsy of ocular tissue and bone marrow trephine biopsy was found normal. We conclude that any suspicious lesion in childhood must be evaluated for retinoblastoma. Even in older child the retinoblastoma may be localized and may have good visual prognosis.